George Eugene Dodge, A Digest of the Laws and Ordinances of the City of Little Rock, with the Constitution of State of Arkansas, General Incorporation Laws, and All Acts of the General Assembly Relating to the City Page 231 - (:unkn) unknown (General Publisher, 1871)
Prohibited firing or discharging any cannon, gun, fowling piece, pistol, fire-arms, squibs, crackers, or other combustible material. Violators fined not less than two nor more than ten dollars.
--
Keywords: DISCHARGE